N-Selenocyanato-Dibenzenesulfonimide: A New Electrophilic Selenocyanation Reagent - Zhu, Deng; Ye, Ai-Hui; Chen, Zhi-Min (Synthesis, 2021)
A new electrophilic selenocyanation reagent N-selenocyanato-dibenzenesulfonimide was readily prepared in two steps from commercially available dibenzenesulfonimide for the first time. A variety of electrophilic selenocyanato reactions of nucleophiles have been achieved using it as selenocyanato source under mild and simple conditions. Numerous SeCN-containing compounds were obtained in moderate to excellent yields. Meanwhile, a Lewis acid mediated tandem selenocyanation/cyclization reaction of alkenes with phenols, which provided simple methods for the formation of various SeCN-containing chromanes and dihydrobenzofurans in moderate to good yields, has also been developed.
Keywords: N-selenocyanato-dibenzenesulfonimide; electrophilic selenocyanation; chromane; dihydrobenzofuran; organoselenium compound